Multiorgan involvement and management in children with Down syndrome. (24th January 2020) - Lagan, Niamh; Huggard, Dean; Mc Grane, Fiona; Leahy, Timothy Ronan; Franklin, Orla; Roche, Edna; Webb, David; O' Marcaigh, Aengus; Cox, Des; El-Khuffash, Afif; Greally, Peter; Balfe, Joanne; et al.
Abstract: Aim: To review multiorgan involvement and management in children with Down syndrome (DS). Methods: A literature review of articles from 1980 to 2019 using the MEDLINE interface of PubMed was performed using the following search terms‐ [Down syndrome] or [Trisomy 21] AND [Cardiology] or [Respiratory] or [neurodevelopment] or [epilepsy] or [musculoskeletal] or [immune system] or [haematological] or [endocrine] or [gastrointestinal] or [ophthalmological] or [Ear Nose Throat] or [dermatology] or [renal]. Results: Congenital heart disease particularly septal defects occur in over 60% of infants with DS and 5%‐34% of infants develop persistent pulmonary hypertension of the newborn irrespective of a diagnosis of congenital heart disease. Early recognition and management of aspiration, obstructive sleep apnoea and recurrent lower respiratory tract infections (LRTI) could reduce risk of developing pulmonary hypertension in later childhood. Children with DS have an increased risk of autistic spectrum disorder, attention deficit disorder and epilepsy particularly infantile spasms, which are associated with poor neurodevelopmental outcomes. Congenital anomalies of the gastrointestinal and renal system as well as autoimmune diseases, coeliac disease, arthropathy, thyroid dysfunction fold diabetes mellitus and dermatological conditions are more common. Hearing and visual anomalies are also well recognised association with DS (Table 1). Conclusion: Children with DS are at an increased risk of multiorgan comorbidities. Organ‐specific health surveillance may provide holistic care for the children and families with DS throughout childhood.